2018
DOI: 10.2106/jbjs.18.00314
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Is Efficacious at Decreasing the Rate of Blood Loss in Adolescent Scoliosis Surgery

Abstract: Background: Tranexamic acid (TXA) is an antifibrinolytic drug that reduces surgical blood loss. Evidence supporting its efficacy in surgery for adolescent idiopathic scoliosis is not robust. This trial was designed to validate the clinical efficacy of TXA in surgery for adolescent idiopathic scoliosis. Methods: This institutional review board-approved prospective double-blinded trial involved 111 patients with adolescent idiopathic scoliosis who were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
94
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 35 publications
0
94
3
Order By: Relevance
“…18 In a study in which intraoperative TXA was used at a loading dose of 50 mg/kg and infusion dose of 10 mg/kg/h in adolescent idiopathic scoliosis patients, it was reported that intraoperative blood loss decreased by 27% compared with that in the placebo group and that none of the patients developed postoperative complications such as thromboembolic events or clinical seizures. 9 In another study, TXA was reported to reduce intraoperative blood loss when administered at a loading dose of 100 mg/kg and infusion dose of 10 mg/kg; furthermore, no negative side effects were observed. 8 The administration dose of TXA varies between 10 and 100 mg/kg for loading dose and between 1 and 10 mg/kg/h for continuous infusion dose.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…18 In a study in which intraoperative TXA was used at a loading dose of 50 mg/kg and infusion dose of 10 mg/kg/h in adolescent idiopathic scoliosis patients, it was reported that intraoperative blood loss decreased by 27% compared with that in the placebo group and that none of the patients developed postoperative complications such as thromboembolic events or clinical seizures. 9 In another study, TXA was reported to reduce intraoperative blood loss when administered at a loading dose of 100 mg/kg and infusion dose of 10 mg/kg; furthermore, no negative side effects were observed. 8 The administration dose of TXA varies between 10 and 100 mg/kg for loading dose and between 1 and 10 mg/kg/h for continuous infusion dose.…”
Section: Discussionmentioning
confidence: 94%
“…11 Goobie et al reported that the blood loss amount per hour was 190 ± 73 ml/h in the TXA group and 230 ± 80 ml/h in the placebo group in the intraoperative period in adolescent idiopathic scoliosis patients. 9 They used the TXA at a loading dose of 50 mg/kg and a maintenance dose of 10 mg/kg/hour. Lykissas et al reported that the mean intraoperative blood loss was significantly lower in the receiving high doses (100 mg/kg bolus dose and infusion dose of 10 mg/kg) TXA (537 ml) than in the placebo group (1245 ml).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Grant et al on the comparative e cacy of high-dose TXA (20mg/kg loading, 10mg/kg/hr maintenance) vs. low-dose TXA (10mg/kg loading, 1mg/kg/hr maintenance), the authors reported that high-dose TXA showed a trend toward a reduction in transfusion requirements compared to low-dose TXA [43]. Based on the above data, literature from adult populations, and our own clinical experience, we use a loading dose of 50mg/kg and a maintenance dose of 5mg/kg/hr [44]. Analogous to systemic TXA, topical TXA has been used in various surgical specialties to decrease perioperative blood loss.…”
Section: Discussionmentioning
confidence: 99%